Blenderella character modeling in Blender 2.5 ([Amsterdam, the Netherlands] Blender Foundation, 2011)
In this DVD, Angela Guenette walks you through her approach on modeling a character within Blender 2.5. She demonstrates the tools used in Blender and techniques on how to create efficient topology with clean edge flow. This will facilitate the creation of facial and body deformation for rigging and animation use.
DVD
Requirements: Any Blender 2.5x (or newer) downloaded from Blender.org will do. Requires a good understanding of modeling basics in Blender. It is also highly recommended to study anatomy books from the masters, and take life drawing classes for a thorough understanding of the fundamentals. This DVD is not intended to teach anatomy or how to design a character.
DVD includes 9 references images from 3d.sk (used with permission from 3d.sk and are marked with their copyright), prepared background images, concept designs, and .blend file of final completed character model.
Contents: 01. Preparing Reference Images in Gimp: 01_Head; 02_Body; 03_Hand--02. Modeling the Head:01_Eyeball and Cornea; 02_Setting up Background Images; 03_Eye Socket Blocking; 04_Nose Blocking; 05_Mouth Blocking; 06_Eyeball Fitting; 07_Eye Socket Detailing; 08_Mouth Detailing; 09_Nose Detailing; 10_Cheeks, Jaw, Forehead, Scalp; 11_Neck; 12_Shaping; 13_Ear; 14_Final Shaping; 15_Geometry Eyelashes--03. Modeling the Body: 01_Setting Up Background Images; 02_Torso; 03_Pelvis; 04_Leg; 05_Arm; 06_Fingers; 07_Hand and Thumb; 08_Rest Pose--04. Modeling the Geometry Hair: 01_Base; 02_Strands--05. Modeling the Clothing: 01_Pants; 02_Shirt; 03_Boot; 04_Masking under Clothing; 05_Shirt2 and Corset; 06_Boot Detailing; 07_Corset Detailing; 08_Pants Finishing--06. Wrap Up: 01_Wrap Up.
Keywords: Computer animation; Computer simulation; Computer graphics; Three-dimensional display systems